PENGARUH PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA PENGGUNAAN KARTU INDOSAT DI KECAMATAN CERME - Putri Ega Selvya; Asri Rejeki; Citrawanti Oktavia (unprimdn.ac.id, 2024)
This study aims to determine the effect of perceived price and service quality on customer satisfaction when using an indosat card. This study uses quantitative approach, through the correlational method. The respondents of this study are residents of Cerme Subdistrict Indosat card users. In sampling through nonprobability sampling using incidental sampling technique. A total of 151 respondents. Scale validity test using content validity. Reliability test using Alpha Cornbach. Data analysis using multiple linear regression tests with IBM Statistical Program For Social Science (SPSS) for windows version 21. From this study, the results obtained are the simultaneous influence between price perceptions and service quality on customer satisfaction of Indosat card users in Cerme sub-district residents with a significance value of 0.000 (p <0.05). In the regression analysis test, a significant value of 0.021 (p <0.05) was obtained, which means that there is no influence between price perceptions on customer satisfaction. The regression test obtained a significance value of 0.232 (p>0.05) which means that there is an effect of service quality on customer satisfaction. The R Square (R2) test results show a figure of 0.201, which means that the price perception and service quality variables contribute 21.1% to the customer satisfaction variable, while the remaining 79.9% is influenced by other variables not examined in this study.